Changes in land use practices influence soil sulfur fractions and their bioavailability - Padhan, Dhaneshwar; Rout, Pragyan Paramita; Sen, Arup (Frontiers in Sustainable Food Systems, 2023)
Changes in land use practices may affect the distribution of soil sulfur (S) fractions and their bioavailability. Therefore, this study was undertaken to assess the influence of different land use changes on the distribution of soil S fractions and their bioavailability for plant nutrition. Soil samples from farmers’ fields with different land use practices such as rice-mustard-jute (R-M-J), rice-lentil-jute (R-L-J), rice-lentil-sesame (R-L-S), rice-vegetable-jute (R-V-J), and rice-potato-green gram (R-P-G) were collected and analyzed for different fractions of S. The bioavailability of S was assessed by extracting the soil with six different extractants (acidic, neutral, and alkaline) with different extraction modes and chemistry. The results showed that changes in land use practices could influence the distribution of soil S fractions and their bioavailability. Organic S was the dominant fraction, accounting for 93.5% of total S across land use practices. The inorganic S fraction (water-soluble, sorbed, and occluded) varied significantly among the land use practices. Among the inorganic fractions, the water-soluble fraction was the dominant fraction across the land use practices. The bioavailability of S, as assessed by different chemical extractants, was in the following order: sodium hydrogen carbonate (NaHCO3) > mehlich-3 > ammonium bicarbonate-diethylenetriamine penta-acetic acid (AB-DTPA) > ammonium acetate-acetic acid (NH4Ac-HOAc) > calcium dihydrogen phosphate Ca(H2PO4)2 > calcium chloride (CaCl2). By establishing relationships between extractable S and soil S fractions, it was observed that all the extractants could obtain S from the water-soluble, sorbed, and organic S fractions, with little extractability from the occluded fraction. Among the extractants tested, mehlich-3 extracted a similar amount of S corresponding to the inorganic fraction across the land use practices. It also maintained positive relationships with different fractions of S, and as a multi-nutrient extractant, its use in routine soil testing can be recommended.